On the cis to trans isomerization of prolyl-peptide bonds under tension - Chen, Jian; Gräter, Frauke (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2012)
The cis peptide bond is a characteristic feature of turns in protein structures and can play the role of a hinge in protein folding. Such cis conformations are most commonly found at peptide bonds immediately preceding proline residues, as the cis and trans states for such bonds are close in energy. However, isomerization over the high rotational barrier is slow. In this study, we investigate how mechanical force accelerates the cis to trans isomerization of the prolyl-peptide bond in a stretched backbone. We employ hybrid quantum mechanical/molecular mechanical force-clamp molecular dynamics simulations in order to describe the electronic effects involved. Under tension, the bond order of the prolyl-peptide bond decreases from a partially double toward a single bond, involving a reduction in the electronic conjugation around the peptide bond. The conformational change from cis to extended trans takes place within a few femtoseconds through a nonplanar state of the nitrogen of the peptide moiety in the transition state region, whereupon the partial double-bond character and planarity of the peptide bond in the final trans state is restored. Our findings give insight into how prolyl-peptide bonds might act as force-modulated mechanical timers or switches in the refolding of proteins.
Gesehen am 29.10.2018